Complete Genome Sequence and Analyses of the Subgenomic RNAs of Sweet Potato Chlorotic Stunt Virus Reveal Several New Features for the Genus Crinivirus - Kreuze, J. F. (American Society for Microbiology, 2002)
The complete nucleotide sequences of genomic RNA1 (9,407 nucleotides [nt]) and RNA2 (8,223 nt) of Sweet potato chlorotic stunt virus (SPCSV; genus Crinivirus, family Closteroviridae) were determined, revealing that SPCSV possesses the second largest identified positive-strand single-stranded RNA genome among plant viruses after Citrus tristeza virus. RNA1 contains two overlapping open reading frames (ORFs) that encode the replication module, consisting of the putative papain-like cysteine proteinase, methyltransferase, helicase, and polymerase domains. RNA2 contains the Closteroviridae hallmark gene array represented by a heat shock protein homologue (Hsp70h), a protein of 50 to 60 kDa depending on the virus, the major coat protein, and a divergent copy of the coat protein. This grouping resembles the genome organization of Lettuce infectious yellows virus (LIYV), the only other crinivirus for which the whole genomic sequence is available. However, in striking contrast to LIYV, the two genomic RNAs of SPCSV contained nearly identical 208-nt-long 3′ terminal sequences, and the ORF for a putative small hydrophobic protein present in LIYV RNA2 was found at a novel position in SPCSV RNA1. Furthermore, unlike any other plant or animal virus, SPCSV carried an ORF for a putative RNase III-like protein (ORF2 on RNA1). Several subgenomic RNAs (sgRNAs) were detected in SPCSV-infected plants, indicating that the sgRNAs formed from RNA1 accumulated earlier in infection than those of RNA2. The 5′ ends of seven sgRNAs were cloned and sequenced by an approach that provided compelling evidence that the sgRNAs are capped in infected plants, a novel finding for members of the Closteroviridae.